Development of Tumor Markers for Breast Cancer Immunotherapy - Fang, Qianqian; Shen, Guoshuang; Xie, Qiqi; Guan, Yumei; Liu, Xinlan; Ren, Dengfeng; Zhao, Fuxing; Liu, Zhilin; Ma, Fei; Zhao, Jiuda (Current Molecular Medicine, 2024)
Although breast cancer treatment has been developed remarkably in recent years, it remains the primary cause of death among women. Immune checkpoint blockade therapy has significantly altered the way breast cancer is treated, although not all patients benefit from the changes. At present, the most effective mechanism of immune checkpoint blockade application in malignant tumors is not clear and efficacy may be influenced by many factors, including host, tumor, and tumor microenvironment dynamics. Therefore, there is a pressing need for tumor immunomarkers that can be used to screen patients and help determine which of them would benefit from breast cancer immunotherapy. At present, no single tumor marker can predict treatment efficacy with sufficient accuracy. Multiple markers may be combined to more accurately pinpoint patients who will respond favorably to immune checkpoint blockade medication. In this review, we have examined the breast cancer treatments, developments in research on the role of tumor markers in maximizing the clinical efficacy of immune checkpoint inhibitors, prospects for the identification of novel therapeutic targets, and the creation of individualized treatment plans. We also discuss how tumor markers can provide guidance for clinical practice.
Keywords: cancers in women